Mind-boggling numbers - Rosen, Michael J., 1954-; Patton, Julia (Minneapolis : Lvl Millbrook Press, 2017)
"This book presents a series of goofy questions that will help kids understand various mind-boggling math concepts."--
Ages 7-11.
K to grade 3.
Includes bibliographical references (page 32).
Keywords: Mathematics -- Juvenile literature; Number concept -- Juvenile literature; Mathematics; Number concept